Legislative program of the Socialist Party : record of the work of the socialist representatives in the state legislatures of the United States, 1899-1913 : with account of efforts of the Party in direct legislation - Mills, Ethelwyn (Chicago: Socialist Party, 1914)
"by Ethelwyn Mills Bibliotheek Camille Huysmans"